Perspectives about professionalism among undergraduate students in a medical college in India: A qualitative study - Prasad Tukaram Dhikale; Saurabh RamBihariLal Shrivastava; Srikanth Srinivasan (Wolters Kluwer Medknow Publications, 2020)
Background: Professionalism has been recognized as an important competency of a doctor by various regulatory bodies. Objectives: The purpose of the study was to explore the perceptions of medical undergraduate students and to assess their attitude on professionalism. Materials and Methods: It was a qualitative study in which four focus group discussions were conducted, one for each year of course. Results: A total of seven themes emerged after the qualitative analysis of the data, namely qualities of a good doctor, need of teaching professionalism, ways of learning professionalism by medical students, ways of teaching professionalism, assessment of professionalism, factors promoting professionalism, and factors hindering professionalism. The students perceived that a good doctor should be committed to excellence, responsive and accountable to patients, profession and community, selfless, healthy, good communicator, ethical and law abiding, practice integrity, and social justice. The students preferred to learn professionalism by role modeling by faculties and case-based scenario discussions. Conclusion: Medical undergraduate students should be briefed about the need and importance of professionalism through small-group discussions involving narratives, case scenarios, and role modeling by faculty. Professionalism of both students and faculties should be assessed and appropriate action taken.